Perancangan Interior Perpustakaan Fashion di Ciputra World Mall Surabaya - Ivana Faustine; Stephanus P. Honggowidjaja (Intra, 2019)
Surabaya is a metropolitan city where developments occur continuously over time. The behavior of Surabaya’s people ultimately developed into a lifestyle that could be described as an urban society. This led to the high growth of locations like malls that are for –but not limited to- shopping, gathering, and recreation. One of the developments that is most followed by the society of Surabaya is fashion. Without realizing it, most of the retail stores in malls are related to fashion, from clothes, bags, shoes, and other accessories. Many people only follow trends but lack of understanding regarding the trends. The design of the fashion library in the mall is aimed at the community so that it is easier to create and educate people about fashion. The design concept adapts to the flowing lifestyle patterns of urban society. The design process method is divided into 6 stages, emphatize, define, ideate, prototype, test, and implement. The resulting interior design plays more color, lifting the color of the trend according to the Pantone. These colors are applied to the furniture and interior element.